Postharvest Biology and Technology of Temperate Fruits (Springer International Publishing, 2018)
This edited volume provides insight into temperate fruits, with an emphasis on postharvest physiology, storage, packaging and technologies for maintaining fruit quality. Chapters are devoted to individual fruits and focus on fundamental issues such as methods for maintaining or enhancing quality, minimizing postharvest losses, and recommended technologies to boost demand. Contributions come from experts in the field, making this a key reference for all aspects of postharvest management of temperate fruits. The volume is unique in its focus on the biodiversity, nutritional and health benefits, and postharvest technologies for shelf life enhancement of temperate fruits. Contributing authors address the postharvest biology and technology of individual temperate fruits such as plum, cherry, peach, apricot, apple, pear, quince, loquat, kiwi, persimmon and berries. There has been tremendous growth in the research and development of new techniques to maintain the quality of temperate fruits from farm to table. Contributions from experts in the field cover these recent advances, providing up-to-date and relevant information for researchers, postharvest/fruit technologists, food scientists, postgraduate students, and others working in the industry.